The influence of salary and work facilities on employee performance at the Grand Candi Hotel Semarang - Yustiana, Nikita Putri; Kholil Aswan, Mukhamad (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of salary and work facilities on employee performance, where the object of this research is the Grand Candi Hotel Semarang. Seeing the influence of salary on employee performance. Seeing the influence of work facilities on employee performance and seeing the influence of salary and work facilities on employee performance. This research used a quantitative approach with a sample size of 75 respondents. data retrieval analysis techniques saturated sampling. The analytical data used includes instrument tests consisting of validity and reliability tests, then hypothesis tests consisting of partial tests or t tests, simultaneous tests or F tests coefficient of determinationor R2 test, and multiple linear test. From the research results it was found that there werethe influence of salary on employee performance.the influence of work facilities on employee performance, and there is pThe influence of salary and work facilities on employee performance ingrand temple hotel semarang